Resiliência e engajamento no trabalho em servidores públicos federais - Dal Ongaro, Juliana (2020)
This study aimed to evaluate the relationship between resilience and work engagement at federal civil servants of an educational institution. It is a cross-sectional study, linked to the matrix transcultural adaptation and validation for Brazilian Portuguese language of the Resilience at Work Scale (RAW Scale) approved by the Research Ethics Committee of the Federal University of Santa Maria under CAEE nº 69318117.2.0000.5346. The population consisted of 526 teaching workers and health professionals from a Federal University in the South of Brazil. Data were collected in the period of April to July 2018 through a questionnaire of socio-demographic, labor, habits and health data, Resilience at Work Scale (RAW Scale 25 - Brazil) and the Utrecht Work Engagement Scale - 17. Poisson regression, descriptive statists, relative (%) and absolute (n) frequency were used, through prevalence reasons and their respective confidence periods, to analyze the associations between resilience and work engagement. A significance level of 5% was considered for all tests. There were 287 (54.6%) health professionals and 239 (45.4%) teachers. A moderate level of resilience at work prevailed (n=217; 42.1%), with higher prevalence in the domains living authentically (n=247; 47%) and finding their vocation (n=240; 45.6%). The minor time of work (14%), needing psychological care (20%) and having little leisure time (12%) showed a higher prevalence for low levels of resilience. Regarding to work engagement, low level (n=207; 39.7%), with moderate level for vigor (n=206; 39.3%) dedication (n=202; 38.5%), and low level for concentration (n=194; 37.1%) were evidenced. Servers with ages up to 28 years old (10%) and 29 to 39 years old (6%) and workloads of 30 and 36 hours (8% and 6% respectively) showed a higher prevalence to low engagement at work. It is concluded that workers with low and medium levels of resilience at work, aged up to 28 years old and 29 to 39 years old presented higher prevalence for low engagement. In face of the results, it stands out the importance to the development of future studies that contemplates the positive aspects in the labor environment, in order to provide reflection and promote knowledge to the scientific community as well as instigate the development of strategies to the improvement of workers’ health.